Developing new roles for higher education institutions in structurally-fragmented regional innovation systems - Henning Kroll; Esther Schricke; Thomas Stahlecker (Fraunhofer Institute for Systems and Innovation Research ISI, 2012)
Over the course of the last decade, increasing political emphasis has been placed on the 'third role' of universities and universities of applied sciences in German higher education policy, i.e. to these institutions socio-economic contribution their regional environment. Against this background it is the first central aim of this study to take account of the existing regional activities of higher education institutions in Germany and to establish whether any effects of regional policymakers' and university management efforts to support such activities are already felt at the level of the individual researcher. Based on survey data, we find that a large array of decentralised projects is being performed by individual academics for multiple reasons, but also that evidence of effective centralised incentive-setting for such activities remains limited. Nonetheless, universities have undoubtedly become integrated into strategic considerations of regional co-operation to a stronger degree, as evidenced by a number of publicly supported programmes and the long time implicit 'third role' of universities of applied sciences. Consequently, the second main aim of the paper is to illustrate how such strategic approaches could be designed against the background of the concrete regional demand of the industrial sector in a case study region. With a view to the example of Upper Palatinate in Bavaria, our paper demonstrates how the formerly strict separation of missions and tasks between universities and universities of applied sciences has resulted in a certain structural fragmentation of competences that hinders the development of a substantial third role in the region. Additionally, it suggests some tentative approaches how this situation could be overcome by an increased co-operation between formerly quite separate institutions.
urn:nbn:de:0011-n-1988157
Keywords: 330; University; Research cooperation; Region; Innovation; Upper Palatinate; Germany; Hochschule; Forschungskooperation; Region; Innovation; Oberpfalz; Deutschland